PENGAWASAN KARYAWAN LAUNDRY SECTION DI ANGKASA GARDEN HOTEL PEKANBARU (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
In training a person will be trained to improve skills, abilities, knowledge and behavior. The purpose of training is to provide skills to prospective employees before working, training is also intended to familiarize prospective employees with work. This study aims to determine employee training in the Laundry Section at Angkasa Garden Hotel Pekanbaru which consists of adding new knowledge, honing employee skills, improving skills, increasing sense of responsibility, providing work motivation, increasing obedience, increasing self-confidence, increasing loyalty, know the obstacles that occur before training, and know the continuation of hotel management regarding employee training. The research method used in this research is descriptive qualitative method. In this study, researchers took the number of sources as many as 6 people. This research data collection technique using observation, interviews, and documentation. Based on the results of the research conducted, it can be concluded that the objectives and benefits of employee training are still not maximal, the reason is the lack of attention of hotel management on the skills possessed by employees, the obstacles that occur before training is carried out, and the actions of hotel management regarding employee training planning. periodically. Key word: Employee Training, Housekeeping, Angkasa Garden Hotel Pekanbaru